Human Relaxin‐2 Fusion Protein Treatment Prevents and Reverses Isoproterenol‐Induced Hypertrophy and Fibrosis in Mouse Heart. Issue 24 (17th December 2019) - Sun, Junhui; Hao, Weidong; Fillmore, Natasha; Ma, Hanley; Springer, Danielle; Yu, Zu‐Xi; Sadowska, Agnieszka; Garcia, Andrew; Chen, Ruoyan; Muniz‐Medina, Vanessa; Rosenthal, Kim; Lin, Jia; et al.
Abstract : Background: Heart failure is one of the leading causes of death in Western countries, and there is a need for new therapeutic approaches. Relaxin‐2 is a peptide hormone that mediates pleiotropic cardiovascular effects, including antifibrotic, angiogenic, vasodilatory, antiapoptotic, and anti‐inflammatory effects in vitro and in vivo. Methods and Results: We developed RELAX10, a fusion protein composed of human relaxin‐2 hormone and the Fc of a human antibody, to test the hypothesis that extended exposure of the relaxin‐2 peptide could reduce cardiac hypertrophy and fibrosis. RELAX10 demonstrated the same specificity and similar in vitro activity as the relaxin‐2 peptide. The terminal half‐life of RELAX10 was 7 days in mouse and 3.75 days in rat after subcutaneous administration. We evaluated whether treatment with RELAX10 could prevent and reverse isoproterenol‐induced cardiac hypertrophy and fibrosis in mice. Isoproterenol administration in mice resulted in increased cardiac hypertrophy and fibrosis compared with vehicle. Coadministration with RELAX10 significantly attenuated the cardiac hypertrophy and fibrosis compared with untreated animals. Isoproterenol administration significantly increased transforming growth factor β1 (TGF‐β1)–induced fibrotic signaling, which was attenuated by RELAX10. We found that RELAX10 also significantly increased protein kinase B/endothelial NO synthase signaling and protein S‐nitrosylation. In the reversal study, RELAX10‐treated animals showed significantly reduced cardiac hypertrophy and collagen levels. Conclusions: These findings support a potential role for RELAX10 in the treatment of heart failure.